1980
DOI: 10.3109/00365528009182225
|View full text |Cite
|
Sign up to set email alerts
|

Cysteamine-induced Duodenal Ulcer and Acid Secretion in the Rat

Abstract: Duodenal ulcers can be produced in rats within 24 h by a single subcutaneous administration of cysteamine. To determine the role of gastric acid secretion in the pathogenesis of these ulcers, secretory and pathoanatomic studies were performed in chronic fistula rats ater an ulcerogenic dose of cysteamine. A prolonged increase of acid secretion was seen after cysteamine, reaching fourfold the basal level after 5 h. The acid response lasted for 10 to 11 h. After vagotomy cysteamine-induced acid secretion was mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 9 publications
2
27
0
Order By: Relevance
“…In contrast to with the low dose, the accumulation of gastric contents in response to the high dose of cysteamine gradually in creased, the maximum being reached at 6 hr. Since a delay in gastric emptying was already evident 1 hr after administration, this gradual accumulation appears to be due to the gradual stimulation of gastric acid secretion, as re ported by other authors (21). The maximal volume and amount of acid with the high dose of cysteamine were almost double those with the high dose of mepirizole.…”
Section: Discussionsupporting
confidence: 50%
“…In contrast to with the low dose, the accumulation of gastric contents in response to the high dose of cysteamine gradually in creased, the maximum being reached at 6 hr. Since a delay in gastric emptying was already evident 1 hr after administration, this gradual accumulation appears to be due to the gradual stimulation of gastric acid secretion, as re ported by other authors (21). The maximal volume and amount of acid with the high dose of cysteamine were almost double those with the high dose of mepirizole.…”
Section: Discussionsupporting
confidence: 50%
“…4 The dose required, however, is 700 to 1000 mg/kg body weight or 40 to 60 times the per-kilogram body weight dose that is currently administered at any one time for the treatment of cystinosis. 1,[5][6][7] The exact mechanism by which cysteamine induces ulcerogenesis is unclear, but it likely involves gastric acid-hypersecretion 6,18 secondary to hypergastrinemia. 19 Low intraluminal pH will inhibit gastrin release through a negative feedback loop.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the observations by other investigators (9) who reported the development of microscopic damage in rat duodenal epithelium 4 to 8 hr after administration of cysteamine (280 mg/ kg, p.o.). From various laboratories (22)(23)(24)(25)(26)(27) it was reported that cysteamine at the ulcerogenic dose significantly increased gastric H+ secretion within 1-4 hr in acute or chronic fistula rats, thereby suggesting the close link of increased gastric secretion in the pathogenesis. We also found that cysteamine (100 mg/kg) increased gastric H+ output by about 2-fold of the control values beginning from 2 hr after administration for the following 2 hr.…”
Section: Discussionmentioning
confidence: 99%